2013
DOI: 10.1371/journal.pone.0083087
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Climate Foster Exceptional Opportunities for Species Radiation: The Case of South African Geraniums

Abstract: Climate change is often assumed to be a major driver of biodiversity loss. However, it can also set the stage for novel diversification in lineages with the evolutionary ability to colonize new environments. Here we tested if the extraordinary evolutionary success of the genus Pelargonium was related to the ability of its species to capitalize on the climate niche variation produced by the historical changes in southern Africa. We evaluated the relationship between rates of climate niche evolution and diversif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Our results provide further support to the growing body of evidence that variation in rates of climatic niche evolution are associated with variation in lineage diversification (Kozak and Wiens ; Martínez‐Cabrera and Peres‐Neto ; Title and Burns ). Although more studies are needed to determine the generality of this relationship, these results suggest that, at least at relatively shallow phylogenetic time scales, variation in rates of climatic‐niche evolution may be at least as important to generating variation in diversification rates and species richness among clades as morphological evolution (see Kozak et al.…”
Section: Discussionsupporting
confidence: 84%
“…Our results provide further support to the growing body of evidence that variation in rates of climatic niche evolution are associated with variation in lineage diversification (Kozak and Wiens ; Martínez‐Cabrera and Peres‐Neto ; Title and Burns ). Although more studies are needed to determine the generality of this relationship, these results suggest that, at least at relatively shallow phylogenetic time scales, variation in rates of climatic‐niche evolution may be at least as important to generating variation in diversification rates and species richness among clades as morphological evolution (see Kozak et al.…”
Section: Discussionsupporting
confidence: 84%
“…We suggest that different patterns of trait associations in Pelargonium seem to have been established during the onset of the diversification of the subclades, such that divergent selection at the onset of subclade origin overrode the legacy of prior shared ancestry, but then persisted through subsequent diversification in response to key climatic events that shaped the distributions of major biomes and floras in South Africa during the Oligocene/Miocene (Bakker et al ., ; Verboom et al ., ). Martínez‐Cabrera & Peres‐Neto () found that aridity gradients are associated with Pelargonium species and phylogenetic turnover across South Africa. They suggested that the evolution of Pelargonium clades, especially in the winter rainfall‐dominated GCFR, was a product of the genetic isolation of ancestral populations that diverged into new species that differentiated ecologically in response to the establishment of new summer aridity gradients.…”
Section: Discussionmentioning
confidence: 97%
“…Because the geographic range of species is the most reliable predictor of extinction risk, it is clear why plants from Ocbils are increasingly joining the IUCN Red List as extinct (Martinelli and Moraes 2013). This fact indicates that restoration ecology deserves focused attention for the conservation of these endemic and threatened biotas, such as the Brazilian iron-rich canga in the Brazilian cerrado (Jacobi et al 2007), cobalt-rich grasslands in Congo (Faucon et al 2010), nickel-rich vegetation in New Caledonia (Wulff et al 2013, Losfeld et al 2015, and banded ironstone outcrops in the SWAFR (Gibson et al 2012).…”
Section: Conservation Implications For Biodiversity Of Ocbilsmentioning
confidence: 99%